Modifikasi Model Logisitik Untuk Peramalan Penduduk - Diandra Chika Fransisca (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2018)
The logistics model can be modified by adding migration factors as a function to the population. This function considers the existence of limited human migration and interaction by the ability of environmental carrying capacity. This model can be completed qualitatively by using the method of point balance analysis and quantitatively by using the exact undesired metodediferensial. Both of these methods give the same result. If the intrinsic growth rate is greater than for migration then for a long period of time, the model will depend on intrinsic growth factor, environmental carrying capacity and migration rate. Furthermore, if the intrinsic growth is small rather than migration then for a prolonged period of time, the model will depend on minus intrinsic growth, environmental carrying capacity and immigration. Then, if migration growth is the same as migration then the model becomes Malthus model.